"It shouldn't look aggressive": How conceptions about publics shape the development of mining exploration technologies. (November 2022) - Bleicher, Alena; Häßler, Pauline; David, Martin
Today, industrial-scale mining is a high-tech activity that transforms places and regions by creating massive technological infrastructures. "The public" and its relationship with this industry are seen as increasingly relevant for mining projects; however, the role technologies play in this regard is as yet under-researched. In this article, we use an example from the European Union's Horizon 2020 research program to examine how technoscientific actors build relationships with the public in the context of mining technology development. More precisely, we reveal how the public is conceptualized by technology developers and how such conceptions come into play in technology development projects. We argue that a central aspect of this is the assumption that certain characteristics of the public are variable or stable. While characteristics perceived as stable tend to lead to an adjustment of the technology to suit the attitudes of an imagined public, characteristics perceived as variable cause no technological modifications but do influence the selection of communication strategies.